Study of perinatal asphyxia and its outcome concerning nucleated RBC count in venous blood of term neonates - Dr. Pradeep Kumar Jena; Dr. Himansu Parida; Dr. Banashree Swain; Dr. Mangal Charan Murmu (Pediatric Review: International Journal of Pediatric Research, 2021)
Introduction: Perinatal asphyxia is a serious problem globally and is one of the common causes of neonatal mortality. Worldwide each year four million infants suffer from birth asphyxia. Of these one million die and an equal number develop serious sequelae. Perinatal asphyxia ranks as the second most important cause of neonatal death after infections accounting for about 23% of mortality worldwide.Aim & objective: To establish the level of nucleated red blood cells as an indicator of poor immediate outcome in perinatal asphyxia. Method: It was a case-control study done in the department of pediatrics, S C B Medical College & S V P PG I P, Cuttack.Observation: The NRBC count was significantly higher in neonates with adverse outcomes than in those with favourable outcomes (p-value <0.001). NRBC count cut-off of >27/100 WBC had a sensitivity of 75% and specificity of 95.2% in predicting adverse outcome defined as death, hemiplegia, hypertonia or significant hypotonia, unreliable sucking and seizures resistant to Phenobarbital.Conclusion: Nucleated red blood cell count can be used as a surrogate marker for birth asphyxia. It has a significant negative correlation with Apgar score at one minute and Apgar score at 5minutes & significant positive correlation with severity of hypoxic ischemic-encephalopathy, time is taken for recovery of neurological impairment following birth asphyxia and duration of NICU stay.